Cultural Heritage Conservation Strategy in Singaraja City, Bali: Strengthening City Identity Through Historical and Architectural Approaches - Agus Kurniawan; I Nyoman Nuri Arthana; José Manuel Maniquin (Universitas Udayana, 2025)
Singaraja city has a rich cultural heritage with significant historical, architectural, and social value. This study is a case study that focuses on three main heritage sites, namely the Buleleng Resident House, the State Junior High School Building 1 Singaraja, and the Buleleng Old Port, which represent the colonial heritage and local identity of the city. The main objective of this study is to formulate an integrated strategy for the preservation of cultural heritage, by identifying the main heritage elements and assessing their conservation challenges and opportunities as sub-objectives. A qualitative descriptive-analytical approach is used through field observations, interviews with local stakeholders, and document analysis. The findings show the need for a multidimensional approach that integrates historical conservation, cultural revitalization, community engagement, and cultural tourism development. This study aligns the findings with applicable policy strategies and contributes to the theory of heritage conservation in Indonesia through strategic recommendations for the sustainable management and promotion of urban heritage assets.